LANDASAN SPIRITUAL KEILMUAN DALAM PENDIDIKAN ISLAM - Kasman, Adi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
Islamic education is a very urgent thing in the formation of a person's spiritual foundation. His guidance and direction are religious teachings aimed at making people believe wholeheartedly in the existence of God, obey and obey His commands in the form of worship, and have noble character. By studying Islamic religious education, it is hoped that a person can have good values in himself, so that it can be translated into his daily behavior. In addition, Islamic religious education can also distance a person from doing bad things. The application of Islamic Education is carried out by increasing devotion to God Almighty and noble morals are a manifestation of the faith that everyone believes. Therefore, faith and devotion that are integrated into a person will avoid acts that are destructive, slanderous, and dangerous to the community and are very dangerous for the future unity and unity of the nation. Islamic education is very important in shaping and developing students' character. Religious and moral education must integrate and interact with each other through the social reality that develops in society. Education that contains and is based on religious values is ultimately able to form a whole human being.